2011
DOI: 10.1080/14786410903335190
|View full text |Cite
|
Sign up to set email alerts
|

Effect of myricetin on deoxycorticosterone acetate (DOCA)-salt-hypertensive rats

Abstract: Chronic administration of myricetin (100 and 300 mg kg⁻¹, p.o., for 4 weeks) isolated from Vitis vinifera (Vitaceae) ameliorated hypertension and oxidative stress induced by deoxycorticosterone acetate (DOCA)-salt in rats. Myricetin treatment reduced systolic blood pressure, vascular reactivity changes and reversed the DOCA-induced increase in heart rate. Urinary sodium excretion was significantly decreased in animals treated with myricetin compared to the DOCA group when measured by flame photometer. The cumu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 21 publications
0
22
0
1
Order By: Relevance
“…These inflammatory cytokines could cause disturbed energy metabolism (Schilling et al, ), impaired β‐adrenergic signaling(de Montmollin, Aboab, Mansart, & Annane, ), imbalanced calcium homeostasis (Zhong, Hwang, Adams, & Rubin, ), and excess production of nitric oxide (Stein, Frank, Schmitz, Scholz, & Thoenes, ), all of which resulted in impaired contractility, diastolic dysfunction, reduced cardiac index, and ejection fraction (de Montmollin et al, ; Schilling et al, ; Stein et al, ; Zhong et al, ). In previous studies, myricetin has been showed to protect the mouse or rat heart from isoproterenol induced myocardial infarction(Tiwari, Mohan, Kasture, Maxia, & Ballero, ), ischemia/reperfusion induced injury (Scarabelli et al, ), and hypertension (Borde, Mohan, & Kasture, ), and the underlying mechanism was related to the regulation of Stat1 and oxidative stress (Borde et al, ; Scarabelli et al, ; Tiwari et al, ). In in vitro experiments, myricetin could blunt the activation of NF‐κB and inhibit the production of proinflammatory cytokines in H9C2 cardiomyocytes (Chen & Fan, ) and macrophages (Cho et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…These inflammatory cytokines could cause disturbed energy metabolism (Schilling et al, ), impaired β‐adrenergic signaling(de Montmollin, Aboab, Mansart, & Annane, ), imbalanced calcium homeostasis (Zhong, Hwang, Adams, & Rubin, ), and excess production of nitric oxide (Stein, Frank, Schmitz, Scholz, & Thoenes, ), all of which resulted in impaired contractility, diastolic dysfunction, reduced cardiac index, and ejection fraction (de Montmollin et al, ; Schilling et al, ; Stein et al, ; Zhong et al, ). In previous studies, myricetin has been showed to protect the mouse or rat heart from isoproterenol induced myocardial infarction(Tiwari, Mohan, Kasture, Maxia, & Ballero, ), ischemia/reperfusion induced injury (Scarabelli et al, ), and hypertension (Borde, Mohan, & Kasture, ), and the underlying mechanism was related to the regulation of Stat1 and oxidative stress (Borde et al, ; Scarabelli et al, ; Tiwari et al, ). In in vitro experiments, myricetin could blunt the activation of NF‐κB and inhibit the production of proinflammatory cytokines in H9C2 cardiomyocytes (Chen & Fan, ) and macrophages (Cho et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The antihypertensive activity of myricetin has been demonstrated in vivo . Hypertension and oxidative stress initiated by deoxycorticosterone acetate (DOCA) was reduced after treatment with oral doses of 100 and 300 mg myricetin/kg body weight in rats [ 117 ]. A reduction in systolic blood pressure, changes in vascular reactivity and a reversal of DOCA-induced increase in heart rate was evident.…”
Section: Pharmacological Applicationsmentioning
confidence: 99%
“…Elevated reactive oxygen species-induced oxidative stress had been reported in human and different animal models of hypertension [23][24][25]. Oxidative stress causes the reduction of NO bioavailability due to removing NO by a super oxide radical and decreasing NO synthesis/release from endothelium.…”
Section: Discussionmentioning
confidence: 99%